Epistaxis management: current understanding amongst junior doctors. Issue 3 (19th January 2016) - Fox, R; Nash, R; Liu, Z-W; Singh, A
Abstract: Background: Epistaxis is a common and potentially life-threatening emergency. This survey assesses understanding and confidence in epistaxis management amongst current junior doctors. Method: A cross-sectional study was conducted of foundation year one and two doctors based at three National Health Service trusts within a single region of the UK, assessing basic understanding and procedural confidence. Results: A total of 111 foundation doctors completed this survey. The average duration of undergraduate exposure to otolaryngology was 8.1 days. Forty-one per cent of respondents stated that they would apply pressure to the nasal bones to control epistaxis. Seventy-five per cent lacked confidence in their ability to manage epistaxis. Those with two weeks or more of undergraduate exposure to otolaryngology were more confident than those with one week or less of exposure ( p < 0.0001). Conclusion: Junior doctors lack understanding and confidence in epistaxis management, with patient safety implications. Confidence is associated with the duration of undergraduate exposure to otolaryngology. A minimum emergency safe competency should be a priority during foundation training if not achieved in UK medical schools.